2000
DOI: 10.1046/j.1365-2346.2000.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute pain management: analysis, implications and consequences after prospective experience with 6349 surgical patients

Abstract: An acute pain service (APS) was set up to improve pain management after operation. We attempted to reduce the length of stay in the intensive care unit (ICU) of patients undergoing major surgery and to improve their homeostasis and rehabilitation using a multimodal approach (pain relief, stress reduction, early extubation). Patient-controlled epidural analgesia (PCEA) was a keystone of this approach. If PCEA was not applicable, patients received patient-controlled intravenous analgesia (PCIA) instead. Brachial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
20

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(53 citation statements)
references
References 28 publications
1
32
0
20
Order By: Relevance
“…In a study by Tsui et al, 31 adequate post-operative analgesia was able to reduce overall mortality and hospital mortality, as well as mean hospital stay, in patients after oesophagectomy (n = 578). A study by Brodner et al 32 confirmed these data by demonstrating that the intervention of an acute pain management service was able to reduce the length of ICU stay in surgical patients (n = 5602); regular assessment of pain formed part of this intervention.…”
Section: Discussionmentioning
confidence: 89%
“…In a study by Tsui et al, 31 adequate post-operative analgesia was able to reduce overall mortality and hospital mortality, as well as mean hospital stay, in patients after oesophagectomy (n = 578). A study by Brodner et al 32 confirmed these data by demonstrating that the intervention of an acute pain management service was able to reduce the length of ICU stay in surgical patients (n = 5602); regular assessment of pain formed part of this intervention.…”
Section: Discussionmentioning
confidence: 89%
“…За даними літератури, від значного та помірного больового синдрому в післяопераційному періоді страждають майже 75 % усіх прооперованих пацієнтів [2,6]. При цьому біль після оперативних втручань на кістках та суглобах за інтенсивністю по-сідає друге місце після операцій на органах черевної порожнини, а неадекватна аналгезія спостерігається в 30-50 % пацієнтів [1,6].…”
Section: резюме у статт наведен дан досл д ення е ективност аналгетиunclassified
“…Analgetisch wirksamere, aus diesem Grund aber aufwändigere Verfahren werden im Rahmen eines ASD häufiger praktiziert und kommen auch öfter Patienten auf allgemeinen Pflegestationen zugute [35]. Nur so lassen sich die bei Risikopatienten und nach großen operativen Eingriffen unbestrittenen Vorteile der "epidural analgesia" (EDA) auch nutzen [9,20]. [17,25,29].…”
Section: Akutschmerzdienstunclassified
“…Einem relativ geringen Aufwand sollten hierbei Kriterien, wie Patientenkomfort und -zufriedenheit und eine mögliche Verkürzung der Hospitalisationszeit, als Erfolgsfaktoren gegenübergestellt werden. Daten zeigen, dass v. a. PCEA die Frühmobilisation und damit einen verkürzten Krankenhausaufenthalt ermöglicht; dies führt letztendlich zu einer Kosteneinsparung [9,20]. Miaskowski et al fanden eine durchschnittliche Reduktion der Hospitalisationszeit um ca.…”
Section: Patientenaufklärung Und -Zufriedenheitunclassified